A Fatal Case of Cerebral Melioidosis - Chaudhary, Raina; Singh, Alina; Pradhan, Manoj; Karki, Reeba; Bhandari, Paawan Bahadur (Medical Journal of Shree Birendra Hospital, 2019)
Introduction: Melioidosis is potentially fatal type of infectious disease caused by soil saprophytes Burkholderia pseudomallei. It is endemic to Southeast Asia and Northern Australia. We report the case of Cerebral Melioidosis which was consequences of acute otitis media. Patient was treated with Ceftazidime and Meropenem, despite of that patient died. To the best of our knowledge, this is the first case of cerebral melioidosis from Nepal.